2017
DOI: 10.1007/s11250-017-1341-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary inclusion of graded levels of toasted guar meal on performance, nutrient digestibility, carcass traits, and serum parameters in commercial broiler chickens

Abstract: An experiment was conducted in a completely randomized design to explore the replacement value of toasted guar meal (TGM) for soybean meal (SBM) in commercial broiler diets. Hypothesis was tested by including graded levels (0, 6, 9, 12, 15, and 18% of diet) of TGM to replace maize-SBM on growth performance, apparent nutrient digestibility, carcass traits, and serum parameters. A total of six iso-nitrogenous and iso-caloric diets were prepared, and each diet was fed ad libitum to 12 replicates of five chicks ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The composition of essential amino acids (EAA) Lys, Met, Thr, His, Leu, Ile, Phe, Val, Arg for poultry in SBM was 3.31%, 0.76%, 2.20%,1.48%, 4.25%, 2.55%, 2.77%, 2.63%, 3.92%, respectively (Pach and Nagel, 2018). It seemed that almost all EAA in GM is lower than SBM, except Arg, which is in accordance with Reddy et al (2017) and Pach and Nagel (2018). However, Salma et al (2015) reported that the Lys content in GM is higher than SBM, and Ile content in GM and SBM was equal.…”
Section: Chemical Composition Of Gmsupporting
confidence: 61%
See 3 more Smart Citations
“…The composition of essential amino acids (EAA) Lys, Met, Thr, His, Leu, Ile, Phe, Val, Arg for poultry in SBM was 3.31%, 0.76%, 2.20%,1.48%, 4.25%, 2.55%, 2.77%, 2.63%, 3.92%, respectively (Pach and Nagel, 2018). It seemed that almost all EAA in GM is lower than SBM, except Arg, which is in accordance with Reddy et al (2017) and Pach and Nagel (2018). However, Salma et al (2015) reported that the Lys content in GM is higher than SBM, and Ile content in GM and SBM was equal.…”
Section: Chemical Composition Of Gmsupporting
confidence: 61%
“…The guar bean (Cyamopsis tetragonoloba) is an annual legume belonging to the Fabaceae family, which native to Africa, and now mainly produced in India and Pakistan (Pach and Nagel, 2018). Guar meal (GM) is a byproduct from guar gum industry, obtained after mechanical separation of endosperm from both germ and hull of guar seed (Janampet et al, 2016;Reddy et al, 2017). GM contains approximately 30-60 % protein on dry matter basis (Nidhina and Muthukumar, 2015;Janampet et al, 2016;Reddy et al, 2017;Pach and Nagel, 2018) and its amino acid (AA) composition quite similar to that of ground nut cake (Verma and McNab, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hafsa et al (2015) reported that dietary inclusion of guar meal (25 to 75%) decreased plasma concentrations of total protein and albumin, but increased the plasma concentrations of urea nitrogen, total cholesterol, and triglycerides. Reddy et al (2017) reported that the serum concentration of total cholesterol was increased in broilers fed diets containing toasted guar meal (6 to 18%). Why dietary guar meal inclusion affected some blood nutrient metabolites in broilers but not in swine warrants further investigation.…”
Section: Serum Metabolitesmentioning
confidence: 99%